Social institutions and economic inequality: Modeling the onset of the Kuznets curve - Brais Alvarez-Pereira; Catherine S. E. Bale; Bernardo Alves Furtado; James E. Gentile; Claudius Gräbner; Heath Henderson; Francesca Lipari (Institute for Applied Economic Research (ipea), 2015)
Theoretical models of the Kuznets Curve have been purely analytical with little contribution towards an understanding of the timing of the process and the presence of additional mechanisms affecting its timing. This paper proposes an agent-based version of Acemoglu and Robinson's model of the Kuznets Curve. In extending their analytical framework we include heterogeneity of agents' income and a mating mechanism that together represent elements of social mobility. These two simple changes proved to be enough to shed light on the length and timing before high inequality implies regime change. Thus, this work may contribute to an effective empirical assessment of the Kuznets curve as it explicitly considers the time dimension of the process and the effects of considering social dynamics.
Keywords: B25; C63; D63; D70; 330; Kuznets curve; agent-based model; inequality; institutions